"An auxiliary, not an usurper": John Saunders, Temperance, and Secularisation. (22nd August 2019) - Starling, Nicole
Abstract : In his influential account of the political history of early colonial Australia, Michael Roe identified the temperance movement of the 1830s–1840s as a pivotal factor in the secularisation of Australian culture and institutions. The belief system that drove the movement, he argued, was not traditional Christian doctrine but a "new faith" of "moral enlightenment." In this article I test the validity of Roe's claim, drawing on the work of a more recent generation of historians and sociologists who have argued for more "porous" and "reciprocal" accounts of concepts such as reason, religion, the Enlightenment, and the secular. Its focus is on the writings and activities of John Saunders, whose endeavours on behalf of the temperance cause were such that he was described by his contemporaries as the "life and soul" of the society, the "father" of the movement, and the "apostle of temperance." It examines the role played by key Enlightenment motifs such as improvement, optimism, reason and cooperation within the rhetoric of Saunders's writings and the reasoning that informed his actions, exploring the various and complicated ways in which he articulated the relationship between evangelical religious conviction and the quest for the common good.